A multi‐centre, single‐arm, open‐label study evaluating the safety and efficacy of fixed dose rituximab in patients with refractory, relapsed or chronic idiopathic thrombocytopenic purpura (R‐ITP1000 study). (11th July 2014) - Tran, Huyen; Brighton, Tim; Grigg, Andrew; McRae, Simon; Dixon, Joanna; Thurley, Daniel; Gandhi, Maher K.; Truman, Matt; Marlton, Paula; Catalano, John
Summary The efficacy of a fixed‐dose rituximab schedule was prospectively explored in primary/acute refractory, relapsed or chronic (platelet count >10 × 109/l and ≤50 × 109/l) idiopathic thrombocytopenic purpura (ITP). Patients received two doses of rituximab (1000 mg) on days 1 and 15 and were followed‐up on weeks 1–8, 12, 26, 39 and 52. A total of 122 patients were included in the safety population; efficacy was analysed in 108 patients. Overall response rate (ORR) at week 8, defined as the proportion of patients achieving complete response (CR; platelet count >150 × 109/l) or partial response (PR; platelet count >50 × 109/l) was 44%. Therapeutic response, defined as achieving a response at week 8, with at least a minor response (MR; platelet count >30 × 109/l), sustained up to weeks 26 and 52 and accompanied by a reduction in ITP medications, was achieved in 44% (week 26) and 35% (week 52) of patients, respectively. Treatment was well tolerated with no safety concerns. While this study failed to meet its primary endpoint of an ORR of 50%, the efficacy of two fixed doses of rituximab appear to provide similar efficacy to the standard 375 mg/m2 four‐dose schedule in relapsed/chronic ITP.